Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To algebraically solve the system of equations:
1. [tex]\( y + 5x = x^2 + 10 \)[/tex]
2. [tex]\( y = 4x - 10 \)[/tex]
we proceed through the following steps:
### Step-by-Step Process:
1. Replace [tex]\( y \)[/tex] in the first equation with the expression from the second equation:
[tex]\[ y = 4x - 10 \][/tex]
Substituting into the first equation:
[tex]\[ (4x - 10) + 5x = x^2 + 10 \][/tex]
2. Simplify and combine like terms:
[tex]\[ 9x - 10 = x^2 + 10 \][/tex]
3. Rearrange all terms to set the equation to zero:
[tex]\[ x^2 - 9x + 10 + 10 = 0 \][/tex]
[tex]\[ x^2 - 9x + 20 = 0 \][/tex]
4. Next, write the simplified version of the quadratic equation:
[tex]\[ x^2 - 9x = 0 \][/tex]
So, the detailed options part of the algebraically solving process include:
- Option 3: [tex]\( 0 = x^2 - 9x \)[/tex]
- Option 4: [tex]\( 0 = x^2 - 9x + 20 \)[/tex]
### Verifying One [tex]\( x \)[/tex]-value of the solution:
Given that one [tex]\( x \)[/tex]-value is 4, we can substitute [tex]\( x = 4 \)[/tex] into either equation to find [tex]\( y \)[/tex]:
Substituting [tex]\( x = 4 \)[/tex] in the second equation:
[tex]\[ y = 4(4) - 10 \][/tex]
[tex]\[ y = 16 - 10 \][/tex]
[tex]\[ y = 6 \][/tex]
Therefore, the solution [tex]\( (x, y) = (4, 6) \)[/tex] is valid.
1. [tex]\( y + 5x = x^2 + 10 \)[/tex]
2. [tex]\( y = 4x - 10 \)[/tex]
we proceed through the following steps:
### Step-by-Step Process:
1. Replace [tex]\( y \)[/tex] in the first equation with the expression from the second equation:
[tex]\[ y = 4x - 10 \][/tex]
Substituting into the first equation:
[tex]\[ (4x - 10) + 5x = x^2 + 10 \][/tex]
2. Simplify and combine like terms:
[tex]\[ 9x - 10 = x^2 + 10 \][/tex]
3. Rearrange all terms to set the equation to zero:
[tex]\[ x^2 - 9x + 10 + 10 = 0 \][/tex]
[tex]\[ x^2 - 9x + 20 = 0 \][/tex]
4. Next, write the simplified version of the quadratic equation:
[tex]\[ x^2 - 9x = 0 \][/tex]
So, the detailed options part of the algebraically solving process include:
- Option 3: [tex]\( 0 = x^2 - 9x \)[/tex]
- Option 4: [tex]\( 0 = x^2 - 9x + 20 \)[/tex]
### Verifying One [tex]\( x \)[/tex]-value of the solution:
Given that one [tex]\( x \)[/tex]-value is 4, we can substitute [tex]\( x = 4 \)[/tex] into either equation to find [tex]\( y \)[/tex]:
Substituting [tex]\( x = 4 \)[/tex] in the second equation:
[tex]\[ y = 4(4) - 10 \][/tex]
[tex]\[ y = 16 - 10 \][/tex]
[tex]\[ y = 6 \][/tex]
Therefore, the solution [tex]\( (x, y) = (4, 6) \)[/tex] is valid.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.